Early stages of Margaritifera margaritifera glochidiosis in Atlantic salmon: morphopathological characterization - Castrillo Arias, Pedro Antonio; Varela Dopico, Catuxa; Ondina Navarret, María Paz; Quiroga Berdeal, María Isabel; Bermúdez Pose, Roberto (Journal of Fish Diseases)
This is the peer reviewed version of the following article: Castrillo PA, Varela‐Dopico C, Ondina P, Quiroga MI, Bermúdez R. (2020). Early stages of Margaritifera margaritifera glochidiosis in Atlantic salmon: Morphopathological characterization. J Fish Dis., which has been published in final form at https://doi.org/10.1111/jfd.13100. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions. Freshwater mussels of the order Unionida encyst into the fish mucosa to metamorphose and complete their life cycle, causing a parasitic disease known as glochidiosis. This parasitic stage represents a bottleneck for the survival of naiads, particularly for critical endangered species as Margaritifera margaritifera, however, little is known about the events occurring during this critical stage. Therefore, this study aimed to histologically characterize the development of M. margaritifera glochidiosis in Atlantic salmon to get insight into the pathogenesis of this interaction. Fish exposed to glochidia were sampled during the first 44 days postexposure and organs were observed by stereomicroscopy and light microscopy. Glochidia attached to the gills by pinching the lamellar epithelium, whereupon an acute proliferative branchitis engulfed most of the larvae. However, during the first 14 days, a severe detachment of unviable glochidia occurred, associated with the presence of pleomorphic inflammatory infiltrate and epithelial degeneration. In the cases where larvae remained attached, a chronification of the lesions with none to scarce inflammation was observed. These results provide key information to better understand the complex host-parasite interaction during the early stages of glochidiosis and provide valuable information to optimize artificial rearing of naiads in conservation of threatened freshwater mussel populations. European Project Life Margal Ulla, Grant/Award Number: 09NAT/ES/00514; Strategic Researcher Cluster BioReDes of Xunta de ...